LIBRARY RESEARCH METHODOLOGY IN EDUCATION: FUNDAMENTAL CONCEPTS AND IMPLEMENTATION - Jamaluddin, Muhammad; Rahmatullah, Asep; M. Farid (CV. Jendela Gagasan, 2025)
This study examines fundamental concepts and implementation of library research methodology in educational contexts through systematic methodological review. Utilizing frameworks from Cooper, Hedges, and Valentine, the research analyzes theoretical foundations, systematic approaches, and practical applications of literature review methodology in education. Analysis reveals that library research has evolved from preliminary activity into sophisticated research methodology built upon constructivist epistemology and social constructivist frameworks. Key findings demonstrate three critical dimensions: robust theoretical foundations integrating multiple philosophical perspectives, systematic methodological frameworks ensuring comprehensiveness and rigor, and practical implementation strategies addressing complex educational research questions. The study identifies essential components including systematic search strategies, quality assessment procedures, technology integration, and collaborative approaches. Results indicate that effective implementation requires careful planning, strategic decision-making, and quality assurance procedures. This methodology enables educational researchers to bridge theory-practice gaps, inform evidence-based decision making, and advance educational knowledge systematically